A Symbiotic Relationship Between Lean Production and Ergonomics: Insights From Industrial Engineering Final Year Projects - Alves, Anabela Carvalho; Ferreira, Ana Cristina; Maia, Laura Costa; Leão, Celina P.; Carneiro, Paula (International Journal of Industrial Engineering and Management, 2019)
Lean production is an organisational management model that increases productivity by eliminating wastes (Muda), physical strain or overburden (Muri), and irregularity (Mura) (3M). These last two are related to the way people work, which is frequently harder instead of smarter. LP helps in achieving smart and effective methods of work. This paper aims to illustrate the synergy between LP and ergonomics by the analysis of a set of final year projects developed in the context of master’s degrees dissertations of Industrial Engineering. It is intended to identify in these the symbiotic relationship between LP and ergonomics solutions that promotes smart, safe and effective work methods. Both share similar concerns about people welfare, providing not only tangible benefits but also intangible benefits. Several final year projects, reported in a set of master’s degrees dissertations in Industrial Engineering, were used to explore if and which ergonomic factors were considered in lean projects developed, by final-year engineering graduates, in an industrial environment. The project phase in which this aspect was manifested and the benefits that resulted from these projects were also studied. The analysis and interpretation of the dissertations showed that, even when the work plan for the project did not reflect the study or evaluation of the workers’ conditions in the lean projects, in most cases, this kind of study was performed to provide solutions for reducing the 3M. A lean project implementation only makes sense when people are respected and their work conditions are considered satisfactory. When this is assured, LP and ergonomics contribute to the improvement of the company productivity, moreover when relevant ergonomic aspects are considered in the work proposal planning phase of the lean-related projects. Article history: Received (8-MAR-2019); Revised (24-SEP-2019); Accepted (4-OCT-2019); Published online (8-OCT-2019)